Treatment of typical antibiotics in constructed wetlands integrated with microbial fuel cells: Roles of plant and circuit operation mode. (July 2020) - Wen, Huiyang; Zhu, Hui; Yan, Baixing; Xu, Yingying; Shutes, Brian
Abstract: This study evaluated the removal efficiencies of sulfamethoxazole (SMX), tetracycline (TC) and their common co-existing contaminants, i.e., chemical oxygen demand (COD) and nitrogen in constructed wetlands integrated with microbial fuel cells (MFC-CWs), as affected by plant, circuit operation mode and influent antibiotic loads. The results demonstrated that MFC-CWs with plant and circuit connection exhibited the best performance in SMX and TC removal. The removal percentages for SMX and TC were 99.70–100% and 99.66–99.85% at HRT of 1 d, respectively, in MFC-CWs with plant and circuit connection when the influent SMX and TC concentrations were 5–100 μg L −1 and 5–50 μg L −1 . The removal efficiencies of both SMX and TC were mainly enhanced by the circuit connection, compared to the plants. The presence of plant and circuit connection also accelerated the accumulation of SMX and TC in electrode layers, and the residues of both antibiotics in the anode layer were higher than in the cathode layer. Besides, closed-circuit MFC-CWs showed better COD removal performance than open-circuit MFC-CWs, irrespective of the increasing influent COD and antibiotic concentrations. The NH4 + -N removal in MFC-CWs was mainly promoted by the presence of plants and decreased with increasing influent antibiotic concentrations. Additionally, the bioelectricity generation of planted MFC-CWs was better than in unplanted systems. The coulombic efficiencies in both planted and unplanted MFC-CWs decreased with increasing influent antibiotic concentrations. In summary, MFC-CWs with plant and circuit connection have potential for the treatment of wastewater containing SMX and TC. Graphical abstract: Image 1 Highlights: Presence of plants and circuit connection accelerated SMX and TC removal in MFC-CWs. More SMX and TC accumulated in the anode layer of MFC-CWs than in the cathode layer. Circuit connection enhanced COD removal irrespective of plants or not. Nitrogen removal in MFC-CWs was inhibited by increasing influent antibiotic loads. The presence of plant promoted the bioelectricity generation in MFC-CWs.